Development and innovation in the fracture management of animals - Thilagar, Sundararajan (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2006)
In the early 1920's, veterinary orthopedic cases were just managed with the help of external coaptation and external fixation devices. In many places conventionally trained persons and veterinarians carried out this practice. Subsequently after a better understanding of fracture biomechanism many internal fixation techniques, have been adopted in animals, providing good success rate of the fracture repair in veterinary practice.After the formation of AO/ ASIF, fracture repair has branched out into many channels particularly in dogs ,cats ,horses and exotic pets. The availability of implants also facilitated the increasing demands from the animal owner to take these techniques. The topic is discussed from the history of fracture repair, the status of its use in animals, classification of fracture, biomechanism of fracture, factors responsible for bone healing fracture, enhancing factor for fracture healing and different fixation techniques (both external and internal).